The temporal distribution of race elements in elite swimmers - Kjendlie, P. L.; Haljand, R.; Fjoertoft, O.; Stallman, R. K. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to examine race element (start, turning and finishing) strategies of elite and national level swimmers in short course 100m races. For 56 finalists at the Norwegian junior national (NOR) and the European Short course Championships (EUR) race analysis was performed by videography. Start- (0-15m), turn- (5m in and 10 m out) and finishing time (last 5m) were analyzed for each race, and these times were normalized to the total race time. The results show that EUR swimmers spend less time in starting, turning and finishing together (p<0.001), starting (p<0.05) and during the first turn (p<0.02) compared to NOR swimmers. The top 3 performers of both groups were found to have a stronger finish normalized to their end performance compared to the other finalists.